Systematic Literature Review: Students' Scientific Argumentation Skills in Chemistry Learning - Luthfia Satyaloka; Regina Tutik Padmaningrum (Universitas Negeri Yogyakarta, 2024)
Developing argumentation skills through learning activities needs to be done with the aim that students can provide rational explanations accompanied by the right reasons. Argumentation skills guide students in including evidence, facts and the right theory to support statements to solve a problem. The topic of scientific argumentation skills is important to research. This study aims to identify, evaluate, and review articles from 2014 - 2024 that have the topic of scientific argumentation skills. The method used in this research is Systematic Literature Review (SLR) with supporting questions, namely, factors that affect students' scientific argumentation skills. This research provides an overview of the condition of students' scientific argumentation skills in chemistry learning. The low argumentation ability of students is caused by several factors including students' understanding of the material tested, students' lack of involvement in activities that contain argumentation, cognitive skills and students' experience.